Bipolar thianthrene derivatives exhibiting room temperature phosphorescence for oxygen sensing. (November 2019) - Tomkeviciene, Ausra; Dabulienė, Asta; Matulaitis, Tomas; Guzauskas, Matas; Andruleviciene, Viktorija; Grazulevicius, Juozas Vidas; Yamanaka, Yuri; Yano, Yoshio; Ono, Toshikazu
Abstract: The series of donor-acceptor (D-A) compounds consisting of a thianthrene donor and either a benzophenone or a diphenylsulfone acceptor units were designed and synthesized via Suzuki cross-coupling. By varying the number of donor units, as well as by introducing heavy atom (Br) into the molecular structure the impact of these substituents on the thermal, electrochemical and emissive properties of the compounds was studied. The compound containing two thianthrene units appeared to have higher thermal stability and higher glass transition temperature than monosubstituted derivative. All thianthrenyl substituted benzophenone or diphenylsulfone compounds showed bipolar behavior. Strong room temperature phosphorescence and dual fluorescence-phosphorescence were observed at room temperature. The compounds containing stronger electron acceptor diphenylsulfone demonstrated a two-fold higher photoluminescence quantum yield values up to 19% in rigid Zeonex ® films than that benzophenone derivatives. The crystals of some synthesized compounds demonstrated oxygen sensing ability. Graphical abstract: Image 1 Highlights: Synthesis and influence of different acceptor units on photophysical properties. Room temperature phosphorescence of thianthrene derivatives in rigid Zeonex ® films with long lifetimes is observed. Oxygen sensing ability of the crystalline samples of the synthesized compounds is demonstrated.